Looking for Recognition: Mimicry as a Strategy for Equality Pramoedya Ananta Toer’s Jejak Langkah - Catharina Brameswari; Gabriel Ephifanio Suwanto; Gabriel Fajar Sasmita Aji (Journal of Language and Literature, 2026)
This research investigates mimicry as a postcolonial strategy for achieving equality in Toer’s Jejak Langkah, drawing on Bhabha’s theoretical framework. This study examines how the pribumi strategically use mimicry within the Dutch East Indies to negotiate power. Jejak Langkah reveals multiple layers of how mimicry operates across colonial society. From a top-down perspective, mimicry appears at the societal level in the adoption of colonial model shaping education and political structures. At the community level, it emerges through patterns of interaction with one another. At the personal level, it is reflected in the choice of attire, style, and cultural expression. This research argues that mimicry is not merely imitation or cultural submission but an elaborate strategy used by the colonized to be perceived as an equal. Through Minke’s transformation, Toer symbolizes how the pribumi adopt the culture of the colonizer to gain recognition and authority. This interpretation exposes mimicry not only as a sign of defeat but also a larger approach born out of necessity within colonial society. The findings contribute to postcolonial studies by examining how the pribumi characters navigate cultural dynamics within the colonial environment and how mimicry becomes a tool for survival, recognition, and liberation from oppression. This led to a better understanding of the social context and how conflict emerges within the Dutch East Indies. The findings suggest the use of mimicry is not one-dimensional but layered to serve a means and purpose for the colonized.